Blastocystis sp. Subtype Diversity in Wild Carnivore Species from Spain - Calero Bernal, Rafael; Santín, Monica; Maloney, Jenny G.; Martín Pérez, Manuel; Habela, Miguel A.; Fernández García, Jose L.; Figueiredo, Ana M.; Nájera, Fernando; Palacios, María J.; Mateo Barrientos, Marta; Balseiro, Ana; Barral, Marta; et al. (My University, 2021)
The occurrence and molecular diversity of the stramenopile eukaryote Blastocystis sp. was investigated by PCR and sequencing (Sanger and NGS) methods in 380 faecal specimens of free-living carnivores in Spain. Blastocystis sp. was confirmed in 1.6% (6/380) of the specimens analysed. Two samples from a common genet and a fox were successfully subtyped as ST7 by Sanger. Using NGS, ST14 was found in a fox and a European polecat, ST7 in a fox, and two additional foxes presented mixed infections of ST1/ST2/ST4 and ST1/ ST2/ST7, respectively. Wild carnivore species could act as carriers of zoonotic Blastocystis subtypes.
Keywords: Next generation sequencing; Sanger; wildlife; zoonotic transmission